Stimulasi Tumbuh Kembang Pada Anak Balita dengan Sosial Ekonomi Rendah Selama Pandemi Covid-19 : A Scoping Review - Sari, Diah Ely Permata; Sulistyaningsih, Sulistyaningsih (Jurusan Kebidanan Poltekkes Kemenkes Mamuju, 2022)
Stimulation of growth and development in children under five during the COVID-19 pandemic significantly affects growth and development stimulation disorders. Disorders of growth and development in children under five can be influenced by families who have low socioeconomic status. Therefore, the government is expected to implement additional public health and education policies, especially for those in low-income families. The objective is to review the stimulation of growth and development in children under five with low socioeconomic status during the covid-19 pandemic. Scoping Review methode using the PRISMA-ScR framework; scoping review questions with the PICO framework; search for articles through relevant databases, namely Pubmed, Science Direct and Wiley, Critical Appraisal using the MMAT tool. Based on the 961 search results there are 10 articles that match the inclusion criteria in this study are as follows: original research articles, research studies using this approach qualitative and quantitative, articles published in English or Indonesian, articles published in the last 2 years in 2020-2021 during the COVID-19 pandemic, in this review there are two main themes, namely socio-demographic and child-rearing patterns. Low socioeconomic and low income are factors that stimulate growth and development where the prospects for completion can achieve prosperity and prosperity in resource associations. Stimulation and food limitations are closely related to parenting patterns where parents can fulfill toddlers' nutrition and stimulate their intelligence. During the COVID-19 pandemic, health workers and cross-sectors sought to implement health and early public education specifically for low-income families. However, it is necessary to carry out further research related to low economic status, low income and limited food, because these are the main factors in decreasing growth and development stimulation of children under five during the COVID-19 pandemic.